Genetic aberrations of NLRC5 are associated with downregulated MHC‐I antigen presentation and impaired T‐cell immunity in follicular lymphoma. Issue 2 (14th October 2020) - Gunawardana, Jay; Lee, Justina N.; Bednarska, Karolina; Murigneux, Valentine; de Long, Lilia Merida; Sabdia, Muhammed B.; Birch, Simone; Tobin, Joshua W. D.; Gandhi, Maher K.
Abstract: Follicular lymphoma (FL) is the most common indolent non‐Hodgkin lymphoma. Twenty to twenty‐five percent of FL patients have progression of disease within 24 months. These patients may benefit from immunotherapy if intact antigen presentation is present. Molecular mechanisms impairing major histocompatibility complex class‐I (MHC‐I) in FL remain undefined. Here, by sequencing of 172 FL tumours, we found the MHC‐I transactivator NLRC5 was the most frequent gene abnormality in the MHC‐I pathway. Pyrosequencing showed that epigenetic silencing of the NLRC5 promoter occurred in 30% of cases and was mutually exclusive to copy number loss (CNL) in NLRC5 (∼6% of cases). Hypermethylation and CNLs (" NLRC5 aberrant") had reduced NLRC5 gene expression compared to wild‐type (WT) cases. By NanoString, there was reduced gene expression of the MHC‐I pathway in aberrant tissues, including immunoproteasome components ( PSMB8 and PSMB9), peptide transporters of antigen processing ( TAP1 ), and MHC‐I ( HLA‐A ), compared to WT. By immunofluorescent microscopy, fewer NLRC5 protein‐expressing malignant B‐cells were observed in NLRC5 aberrant tissue sections compared to NLRC5 WT ( P < .01). Consistent with a pivotal role in the activation of CD8 + T‐cells, both CD8 and CD137 strongly correlated with NLRC5 expression (both r > 0.7; P < .0001). Further studies are required to determine whether patients with aberrant NLRC5 have a diminished response to immunotherapy.